K+ Channel Tetramerization Domain 5 kctd5 Protein Regulates Cell Migration, Focal Adhesion Dynamics and Spreading Through Modulation of Ca2+ Signaling and rac1 Activity - Sepulveda-Salas, J; Leiva-Salcedo, D; Riquelme-Pacheco, D (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Cell migration is critical for several physiological and pathophysiological processes. It depends on the coordinated action of kinases, phosphatases, Rho-GTPases proteins, and Ca2+ signaling. Interestingly, ubiquitination events have emerged as regulatory elements of migration. Thus, the role of proteins involved in ubiquitination processes could be relevant to a complete understanding of pro-migratory mechanisms. KCTD5 is a member of Potassium Channel Tetramerization Domain (KCTD) proteins that have been proposed as a putative adaptor for Cullin3-E3 ubiquitin ligase and a novel regulatory protein of TRPM4 channels. Here, we study whether KCTD5 participates in cell migration-associated mechanisms, such as focal adhesion dynamics and cellular spreading. Our results show that KCTD5 CRISPR/Cas9- and shRNA-based depletion in B16-F10 cells promoted an increase in cell migration and cell spreading, and a decrease in the focal adhesion area, consistent with an increased focal adhesion disassembly rate. The expression of a dominant-negative mutant of Rho-GTPases Rac1 precluded the KCTD5 depletion-induced increase in cell spreading. Additionally, KCTD5 silencing decreased the serum-induced Ca2+ response, and the reversion of this with ionomycin abolished the KCTD5 knockdown-induced decrease in focal adhesion size. Together, these data suggest that KCTD5 acts as a regulator of cell migration by modulating cell spreading and focal adhesion dynamics through Rac1 activity and Ca2+ signaling, respectively. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.